Relationship Between Patient Knowledge Level And use Corticosteroid Drugs At Pharmacies X And Y - Fadillah Noviyanti; Hidayah Apriliawan; Aprilia Puteri Santika (International Journal of Health Engineering and Technology, 2026)
Corticosteroids are a class of drugs widely used in healthcare services due to their anti-inflammatory, anti-allergic, and immunosuppressant effects. These drugs are often prescribed in healthcare facilities, including pharmacies. The use of corticosteroids requires a good understanding from patients for safe use. The level of patient knowledge regarding corticosteroid drugs can be influenced by various respondent characteristics, such as age, gender, and occupation. Therefore, it is necessary to conduct research to determine the relationship between respondent characteristics and the level of patient knowledge regarding corticosteroid drugs in healthcare facilities. Objective: This study aims to determine the relationship between the level of patient knowledge and respondent characteristics (age, gender, and occupation) in healthcare facilities in pharmacies. This study is an observational analytical study with a cross-sectional design. Sampling was carried out using an accidental sampling technique on patients who obtained corticosteroid drugs at x Pharmacy and y Pharmacy in December 2025. The number of samples in this study was 100 respondents. The research instruments were a questionnaire on the level of patient knowledge and a questionnaire on respondent characteristics. The study showed that patients' knowledge of corticosteroids ranged from good (51.57%), sufficient (32.63%), and poor (15.78%). Chi-square test results showed no significant association between age, gender, and occupation with patients' knowledge of corticosteroids (p>0.05). There was no association between respondent characteristics (age, gender, and occupation) and patients' knowledge of corticosteroids at health care facilities in pharmacies.